PENINGKATAN PENGETAHUAN MASYARAKAT TENTANG MANFAAT SHOLAT DAN PUASA BAGI KESEHATAN MELALUI MEDIA RADIO - Ani Qomariyah; Eka Yunita Wulandari (LP2M Universitas Ibrahimy, 2022)
Prayer and fasting are obligatory for Muslims. However, many people still see prayer and fasting as merely obligations and activities that consume a lot of energy. For this reason, people need to be given a good understanding of the importance of prayer and fasting from a health perspective. One of the media that is important for the development of the Banyuwangi community is radio, so we conveyed the socialization through Radio VIS FM 101.5. This activity has been carried out on 4 – 6 April 2022 (Ramadhan month 1443 H). The method that has been used in this activity was Asset Based Community Development (ABCD). This activity was talk shows, lectures, discussions, and giving questionnaires. As a result, people who initially had a low understanding of the benefits of prayer and fasting for health (comprehension level was only 35 – 60%), they had a much better level of understanding. Based on the evaluation results that have been carried out, 100% of the people already knew and understood the importance of the benefits of prayer and fasting on health, 95% of the people knew that the prayer movement can nourish joints, bones, and mental health, and 90% of the people understood that when fasting occurred detoxification process of the body and rejuvenation of body cells.